Hybrid Recentering Energy Dissipative Device for Seismic Protection. (22nd September 2014) - Tang, Wenke; Lui, Eric M.
Abstract : A hybrid recentering energy dissipative device that has both recentering and energy dissipation capabilities is proposed and studied in this paper. The proposed hybrid device, referred to as the hybrid shape memory alloy (SMA) recentering viscous fluid (RCVF) energy dissipation device, connects the apex of a chevron brace to an adjoining beam using two sets of SMA wires arranged in series on either side of the brace and a viscous fluid damper arranged in parallel with the SMA wires. The viscous damper is used because being a velocity-dependent device it does not exert any force that counteracts the recentering force from the SMA wires after the vibration of the frame ceases. In the numerical study, the Wilde's SMA constitutive model is used to model the SMA wires, and the Maxwell model is used to simulate the viscous fluid damper. To demonstrate the viability and effectiveness of the proposed hybrid device, comparative studies are performed on several single-story shear frames and a series of four-story steel frames. The results show that the frames equipped with the hybrid device have noticeably smaller peak top story displacements and residual story drifts when subjected to ground motions at three different intensity levels.